Clinical Nurse Specialist as Nurse Researcher: Development of SMART Metrics and Dashboard to Articulate Role. Issue 6 (November 2021) - Mason, Tina M.
Abstract : Purpose: The purpose of this article is to present how metrics and dashboards, using the SMART model, are used to articulate the clinical nurse specialist (CNS) nurse researcher role. Description of the Project: Following the SMART model, a dashboard was created highlighting measurable metrics for each of the 3 spheres of impact to align with the center's nursing strategic plan and initiatives, including Magnet redesignation. Outcome: Metrics reflecting the 3 spheres of impact and corresponding dashboard with successfully met outcomes are presented for the CNS nurse researcher. Conclusion: Metrics and dashboards are important tools that CNSs can use to capture their activities, set goals, and articulate their unique roles to both internal and external stakeholders. Dashboards, such as the one presented, are easily adaptable and can be updated on a regular basis.